Cutaneous squamous cell carcinoma in vertically acquired HIV and epidermodysplasia verruciformis - Linda A. Mandikiyana Chirimuta; Francis J. Ndowa; Margaret J. Pascoe (AOSIS, 2022)
Introduction: Acquired epidermodysplasia verruciformis (EV) is a skin disorder that has been described in individuals with perinatally acquired HIV. Many cases have been identified in sub-Saharan Africa in keeping with the epidemiology of HIV infection compared to the rest of the world, where cases are rare. Epidermodysplasia verruciformis skin lesions may undergo malignant transformation. There are few documented cases of malignant transformation of these skin lesions. We describe a patient with an EV-like skin rash who developed cutaneous squamous cell carcinoma (SCC). Patient presentation: A 25-year-old man, on antiretroviral treatment for 12 years, presented with a generalised skin rash since the age of 11 years, and a 7-month history of a persistent scalp ulcer. He had no history of trauma, radiation or other chronic conditions. Despite an undetectable HIV viral load, he had failed to immune reconstitute (CD4 42 cells/µL). Physical examination revealed a generalised hypopigmented, papular skin rash resembling verruca plana and a 3 cm × 3 cm ulcer with rolled edges on the right parietal region of the scalp. There were no palpable lymph nodes in the head and neck areas. Biopsy of the ulcer revealed moderately differentiated SCC. Management and outcome: Wide local excision of the lesion was done under local anaesthesia and histological analysis confirmed completely excised moderately differentiated SCC. Further examination four weeks later revealed two, smaller, histologically similar scalp lesions which were completely excised. Conclusion: Patients with acquired EV require thorough, frequent examination for skin lesions with possible malignant transformation. Early identification of malignant transformation and treatment with surgical intervention is curative.